Tinjauan Hukum Normatif terhadap Efektivitas Penegakan Hukum dalam Tindak Pidana Perdagangan Orang di Kamboja - Nadya Tania Sagala; Priciliya Deabita Br Sitepu (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the modus operandi of human trafficking involving Indonesian citizens in Cambodia, to examine the legal enforcement challenges against perpetrators who utilize social media and transnational networks and to evaluate the preventive and countermeasures undertaken by the government. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that the main normative issues lie in the ambiguous application of Articles 2, 4 and 12 of Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Human Trafficking in cases involving social media and cross-border jurisdiction, as well as the absence of a firm bilateral agreement between Indonesia and Cambodia. Regulatory weaknesses in Cambodia also hinder the mutual legal assistance process. As operational recommendations, there is a need for implementing regulations that govern the use of social media as electronic evidence, enhanced digital forensic capacity of law enforcement officials and strengthened memoranda of understanding with Cambodia regarding rapid repatriation mechanisms and protection of victim-witnesses.